2013
DOI: 10.1128/jvi.01648-13
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of Rabies Virus into Epithelial Cells by Clathrin-Mediated Endocytosis Depends upon Actin

Abstract: dRabies virus (RABV) causes a fatal zoonotic encephalitis. Disease symptoms require replication and spread of the virus within neuronal cells; however, in infected animals as well as in cell culture the virus replicates in a broad range of cell types. Here we use a single-cycle RABV and a recombinant vesicular stomatitis virus (rVSV) in which the glycoprotein (G) was replaced with that of RABV (rVSV RABV G) to examine RABV uptake into the African green monkey kidney cell line BS-C-1. Combining biochemical stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
87
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(92 citation statements)
references
References 44 publications
4
87
0
Order By: Relevance
“…Since the morphology of the VSV particle dictates the requirement for actin to complete the process of internalization when entering via a clathrin-mediated process (40,48), the lack of a requirement for actin polymerization indicates that HERV-K ENV does not enter via the same clathrin-mediated entry pathway as VSV. Together, these data suggest that HERV-K ENV dictates an entry pathway that is dynamin dependent but clathrin and macropinocytosis independent, which is distinct from what we have observed with other recombinant VSVs (49,54). Available evidence supports the notion that MMTV also enters cells via clathrin-independent endocytic uptake; however, the requirement for dynamin or macropinocytosis is unknown (19).…”
Section: Discussionmentioning
confidence: 34%
“…Since the morphology of the VSV particle dictates the requirement for actin to complete the process of internalization when entering via a clathrin-mediated process (40,48), the lack of a requirement for actin polymerization indicates that HERV-K ENV does not enter via the same clathrin-mediated entry pathway as VSV. Together, these data suggest that HERV-K ENV dictates an entry pathway that is dynamin dependent but clathrin and macropinocytosis independent, which is distinct from what we have observed with other recombinant VSVs (49,54). Available evidence supports the notion that MMTV also enters cells via clathrin-independent endocytic uptake; however, the requirement for dynamin or macropinocytosis is unknown (19).…”
Section: Discussionmentioning
confidence: 34%
“…Clathrin-mediated endocytosis is an entry mechanism for various environmental factors including bacteria, viruses and other particulates (Cureton et al, 2010; Pauly and Drubin, 2007; Pelkmans and Helenius, 2003; Piccinotti et al, 2013; Veiga and Cossart, 2006; Yamauchi and Helenius, 2013). Our data suggest that further experiments might be required to assess whether SWCNT also exploit this cellular entry mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Upon binding of RABV to the cell membrane, the virus is internalized by endocytosis, predominantly via partially clathrin-coated pits and in an actin-dependent manner (Piccinotti et al, 2013), which resembles the mechanism observed for VSV (Cureton et al, 2010). In neurons, following internalization at the axon terminal, incoming RABV virions are actively transported in a retrograde manner towards the cell body with or within vesicles containing p75NTR Klingen et al, 2008).…”
Section: The Rabv G Proteinmentioning
confidence: 96%